Students’ visual-spatial ability in representing single cell epidermis of rhoeo discolor leaf - H Azalia; A Rahmat; E Nuraeni (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
The one of the way to study plant anatomy was taught by observation frommicroscopic object and represented visual-spatially. This study was focused on students visualspatial ability in representing single cell epidermis of Rhoeo discolor leaf. It was conducted with44 undergraduate students who presently enchanting Plant Anatomy. Data was collected usingvisual spatial worksheet and questionnaire. Students was representing cell in three activities: (1)visual representation of two dimentional (2D) on transverse, longitudinal and paradermalincision of epidermis cell; (2) visual representation of three dimentional (3D) that representsthree types of incision; and (3) spatial representation by constructed 3D model of single cellbased on microscopic observation. Several types representation of the plant cell structure wasobserved. There are significant correlation between students ability to representing microscopicobject in 2D to 3D (r=0,504;p<0,05) and representing 3D to 3D model of cell (r=0,460;p<0,05),but there is no significant correlation between students ability in representing 2D to 3D modelof cell (r=0,288;p>0,05). The result shows, there is scaffolding correlation between visualrepresentation ability to spatial representation ability. Several factors are supposed to affect thecorrelation between students visual spatial ability will be explain further in this article.